Coloured dyes wastewater - Azlan, Mawar Marisa; Abduh Algheethi, Adel Ali Saeed; Abdul Kadir, Aeslina (Penerbit UTHM, 2021)
Cosmetic manufacturing is classified into five sections that reduce selling demand namely fragrance, make-up, skincare and others. However, the technologies introduce sustainability building and creatures as conservation of our environment. There also some ways that can be practiced removing these contaminated materials to save the environment.